Portugal Democrático: An Exiles’ Newspaper - Travancas, Isabel (2017)
The purpose of this article is to present the newspaper Portugal Democrático (Democratic Portugal) through its history, its style and format. It is a periodical publication produced in São Paulo by Portuguese exiles during the dictatorship of Antônio Salazar (1926-1974). The newspaper began to circulate in 1956 and came to an end in 1975, a year after the Carnation Revolution that occurred on April 25, 1974. Fighting the Salazar dictatorship outside Portugal was the reason for the creation of the newspaper in Brazil, where it also had the collaboration of Brazilian journalists and intellectuals. This paper analyzes the newspaper Portugal Democrático both in its political aspect and in its editorial feature and concludes that the paper played a greater role than informative. It was an important part of the international opposition movement and resistance to Salazar's dictatorial regime.O objetivo deste artigo é apresentar o jornal Portugal Democrático através de sua história, de seu estilo e formato. Trata-se de uma publicação periódica produzida em São Paulo por exilados portugueses durante a ditadura de Antônio Salazar (1926-1974). O jornal começou a circular em 1956 e chegou ao fim em 1975, um ano depois da Revolução dos Cravos ocorrida em 25 de abril de 1974. Lutar contra a ditadura salazarista fora de Portugal foi o motivo da criação do jornal no Brasil, onde contou com a colaboração de jornalistas e intelectuais brasileiros. O trabalho analisa o jornal Portugal Democrático tanto em seu aspecto político quanto em sua feição editorial e conclui que o periódico teve um papel maior do que informativo. Ele foi parte importante no movimento internacional de oposição e resistência ao regime ditatorial de Salazar.El objetivo de este artículo es dar a conocer el periódico Portugal Democrático a través de su historia, de su estilo y formato. Se trata de una publicación periódica producida en São Paulo por los exiliados portugueses durante la dictadura de Antônio Salazar (1926-1974). El periódico comenzó a circular en 1956 y dejó de publicarse en 1975, un año después de la Revolución de los Claveles el 25 de abril de 1974. La lucha contra la dictadura salazarista que se llevó a cabo fuera de Portugal fue el motivo de la creación del periódico en Brasil, en la que colaboraron periodistas e intelectuales brasileños. Este trabajo analiza el periódico tanto en el aspecto político como en el editorial. Una de las conclusiones principales es la gran relevancia que el periódico tuvo más allá de su rol informativo, formando parte del movimiento internacional de oposición y resistencia al régimen dictatorial de Salazar.